Enhancing Students’ Science Literacy Skills; Implications for Scientific Approach in Elementary School - Kartimi Kartimi; Widodo Winarso (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractScience literacy skills of elementary school students in the era of 21st-century learning are indispensable, scientific literacy skills can be improved through the application of a scientific approach. This study aims to analyze the scientific literacy ability of elementary school students through the application of a scientific approach. The experimental method with a pretest-posttest group design was used in this study. Simple Random Sampling, consisting of an experimental class and a control class, was applied to elementary schools in Cirebon, Indonesia. The scientific literacy skills test (TOSLS) measures students' literacy skills, while the observational assessment measures students' responses to the scientific approach. The data analysis technique used independent sample T-Test and Mann-Whitney U. The results showed that students' learning activities in the application of scientific learning experienced an increase in scientific literacy skills with very strong criteria. Student learning activities in the experimental class have a higher percentage over the control class. The research hypothesis shows that there is a difference in the improvement of students' scientific literacy skills between the experimental class and the control class of elementary school students. Thus, the application of a scientific approach contributes to students' scientific literacy skills.Keywords: scientific literacy, scientific approach, science education.Â AbstrakKeterampilan literasi sains siswa sekolah dasar di era pembelajaran abad 21 sangat diperlukan. Keterampilan literasi sains dapat ditingkatkan melalui penerapan pendekatan saintifik. Penelitian ini bertujuan untuk menganalisis kemampuan literasi sains siswa sekolah dasar melalui penerapan pendekatan saintifik. Metode eksperimen dengan desain pretest-posttest group design digunakan dalam penelitian ini. Simple Random Sampling, terdiri dari kelas eksperimen dan kelas kontrol di sebuah sekolah dasar di Indonesia. Tes keterampilan literasi sains (TOSLS) mengukur kemampuan literasi siswa, sedangkan penilaian observasional mengukur respons siswa terhadap pendekatan saintifik. Teknik analisis data menggunakan independent sample T-Test dan Mann-Whitney U. Hasil penelitian menunjukkan bahwa aktivitas belajar siswa ketika diterapkan pendekatan saintifik mengalami peningkatan keterampilan literasi sains dengan kriteria sangat kuat. Aktivitas belajar siswa pada kelas eksperimen memiliki persentase yang lebih tinggi dibandingkan dengan kelas kontrol. Hipotesis penelitian menunjukkan bahwa terdapat perbedaan peningkatan kemampuan literasi sains siswa antara kelas eksperimen dan kelas kontrol siswa SD. Dengan demikian, penerapan pendekatan saintifik berkontribusi terhadap kemampuan literasi sains siswa.Kata kunci: literasi ilmiah, pendekatan ilmiah, pendidikan sains.